Profiling and validation of individual and patterns of Chlamydia trachomatis-specific antibody responses in trachomatous trichiasis - Pickering, Harry (Parasit Vectors, 2017)
BACKGROUND: Ocular Chlamydia trachomatis (Ct) infection causes trachoma, the leading infectious cause of blindness. A Ct D/UW3 proteome microarray and sera from Gambian adults with trachomatous trichiasis (TT) or healthy matched controls previously identified several novel antigens, which suggested differential recognition in adults with TT. METHODS: We re-analysed this serological microarray data using more robust microarray analysis techniques accounting for typical problems associated with highly dimensional data. We examined the Ct-specific antibody profile concerning the overall diversity of responses, antigen expression stage and cellular localisation of antigens. We tested differentially recognised antigens by further serological testing of the screened sera and used larger independent sample sets for validation. RESULTS: Antibody responses identified High-Performance on antigens expressed early and late in the Ct developmental cycle and those secreted or localised to the outer membrane. Eight antigens were preferentially recognised by scarred individuals and one antigen by healthy individuals. Three of these antigens, two associated with scarring (CT667 and CT706) and one healthy-associated (CT442), were not associated with the presence or absence of scarring following specific serological testing of the arrayed sera and sera from larger, independent case-control cohorts. CONCLUSIONS: This study identified focussed Ct-specific antibody profiles targeting proteins expressed during entry and exit from cells and localised to interact with the host. A small panel of antibody responses could discriminate between adults with and without TT in a trachoma-endemic community. Heterogenous responses in the independent validation of these antibody targets highlighted the need for large sample sizes, clearly defined clinical phenotypes and follow-up work. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-017-2078-8) contains supplementary material, which is available to authorized users.